SYMBOLIC OR SUBSTANTIVE? CARBON DISCLOSURE AND EARNINGS QUALITY: THE MODERATING ROLE OF CORPORATE GOVERNANCE MECHANISMS - Ari Dewi Cahyati; Hadi Mahmudah; Annafi Indra Tama; Anisa Putri (EKUITAS (Jurnal Ekonomi dan Keuangan), 2025)
Abstract This study examines whether carbon disclosure (CD) in the Indonesian reflects a symbolic effort to project environmental responsibility or a substantive commitment that enhances earnings quality. Grounded in stakeholder theory and agency theory, the research investigates the direct effects of CD and corporate governance (CG) on earnings management (EM), as well as the moderating role of CG in this relationship. Using Partial Least Squares Structural Equation Modeling (PLS-SEM) with control variables—Current Ratio, Leverage, Market-to-Book Ratio (MKTB), and Size—the study finds that CD has a positive and significant effect on EM, indicating that it can be strategically employed as a symbolic tool to obscure opportunistic behavior. In contrast, CG has a negative and significant impact on EM, supporting its role as a mechanism to limit managerial opportunism and improve earnings quality. The interaction terms CG and CD are also negative and significant, suggesting that strong governance can mitigate the symbolic use of CD by aligning disclosures more closely with substantive environmental performance. Among the control variables, only the Current Ratio significantly affects EM. These findings underscore the need for robust governance structures to ensure that voluntary carbon disclosures, transition from symbolic gestures to genuine accountability.